ANALISIS KINERJA PEGAWAI DI SMAN 4, SMAN 12, SMKN 11 MEDAN DALAM MENJALANKAN TUGAS SEBAGAI APARATUR SIPIL NEGARA (ASN) - Elsa Mayora; Hodtua Lestari; Kartika Bestari (FKIP, Universitas Palangka Raya, 2023)
The purpose of this study was to determine the performance of the State Civil Apparatus, who were at SMAN 4, SMAN 12, SMKN 11 Medan. What is the role of the teacher in carrying out his duties as a State Civil Apparatus and to know the rights and obligations of the State Civil Apparatus in schools. The research technique used is a qualitative descriptive analysis technique with interview techniques. The results of the research are based on the analysis that has been carried out by the author about the performance of the state civil apparatus (ASN) at SMAN 4 MEDAN, SMA 12 MEDAN and SMKN 11 MEDAN, it can be concluded that, the quality of work produced by school principals, teachers, administrative staff, security guards, and cleaning service is quite optimal, but still needs improvement in carrying out tasks so that it is more optimal so that the quality of work increases. Employee time in completing work completion targets is something that must be done in order to create an effective organization in achieving goals. The performance of school principals, teachers, administrative staff, security guards, and cleaning services is considered quite good in schools, marked by the ability of employees to complete work and also a high sense of responsibility as state civil servants (ASN).